2008
DOI: 10.1089/ars.2007.1916
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants as Potential Therapeutics for Lung Fibrosis

Abstract: Interstitial lung disease encompasses a large group of chronic lung disorders associated with excessive tissue remodeling, scarring, and fibrosis. The evidence of a redox imbalance in lung fibrosis is substantial, and the rationale for testing antioxidants as potential new therapeutics for lung fibrosis is appealing. Current animal models of lung fibrosis have clear involvement of ROS in their pathogenesis. New classes of antioxidant agents divided into catalytic antioxidant mimetics and antioxidant scavengers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
89
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 221 publications
(193 reference statements)
2
89
0
2
Order By: Relevance
“…The delayed nature of the ROS response suggests a reason why antioxidants such as N-acetylcysteine, GSH, or AEOL 10150 have beneficial effects even when administered after CEES exposure. The ability of a catalytic antioxidant like AEOL 10150 that has been show to have both SOD and catalase activity (Milano and Day, 2000;Day, 2008) to rescue cells from CEES further demonstrates a role for ROS in CEES injury.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The delayed nature of the ROS response suggests a reason why antioxidants such as N-acetylcysteine, GSH, or AEOL 10150 have beneficial effects even when administered after CEES exposure. The ability of a catalytic antioxidant like AEOL 10150 that has been show to have both SOD and catalase activity (Milano and Day, 2000;Day, 2008) to rescue cells from CEES further demonstrates a role for ROS in CEES injury.…”
Section: Discussionmentioning
confidence: 99%
“…We have developed a class of small-molecule metalloporphyrin catalytic antioxidants that possess both high SOD and catalase activities among other detoxifying properties (Day, 2008). Metalloporphyrins have also shown promise as therapeutic agents in several ROS-mediated animal models of human disease states (Day, 2004).…”
mentioning
confidence: 99%
“…Consequently, disease-promoting processes that are at least in part caused by oxidative damage can be targeted by increasing the antioxidant defense, for example, by the intake of, or supplementation with, antioxidants (19,28,59). Consistently, antioxidant treatment with the SOD mimetic EUK207 during the first month after thorax irradiation was able to protect against excessive collagen synthesis during the fibrotic stage (25-30 weeks) (29).…”
Section: Murine Wt Bm (Xrt/bm) Cells From C57bl/6 Donor Mice Into Thementioning
confidence: 99%
“…Other researcher reported that bleomycin increases lung epithelial cell apoptosis in a reactive oxygen species (ROS)-dependent manner [28]. BLM-induced pulmonary fibrosis was explained by some authors who reported that the chemotherapeutic mechanism of BLM results from the chelation of iron ions with oxygen, which leads to production of DNA-cleaving superoxide, and also hydroxide free radicals [29].…”
Section: Discussionmentioning
confidence: 99%